Implementing Skin‐to‐Skin Contact in the Operating Room Following Cesarean Birth. (18th August 2014) - Grassley, Jane S.; Jones, Judith
<x xml:space="preserve">Abstract</x> This column shares the best evidence‐based strategies and innovative ideas on how to facilitate the implementing of EBP principles and processes by clinicians as well as nursing and interprofessional students. Guidelines for submission are available at http://onlinelibrary.wiley.com/journal/10.1111/(ISSN)1741‐6787